The impact of COVID-19 on cultural and arts activities: evidence from a large-scale micro-level survey in South Korea - Shin, Seonho (Journal of Cultural Economics, 2025)
Despite consensus in the literature regarding the importance of culture and arts, as well as their vulnerability to economic shocks, few empirical studies assess the degree to which they have been affected adversely by the COVID-19 pandemic. This study thus quantitatively measures the impact of COVID-19 on people’s cultural engagement in South Korea. Various econometric methods are applied to South Korea’s large-scale Culture and Arts Activity Survey dataset, which is nationally representative and provides micro-level detail. Results suggest that COVID-19 made South Korean people substantially and significantly less likely to participate in cultural and arts activities—by 15 to 17 percentage points for venue activities and 24 to 25 percentage points for outdoor activities. Strong heterogeneity, however, seems to exist depending on an individual’s gender, age, education, income, and early exposure to the arts. Interestingly, the pandemic rather raised people’s likelihood of visiting a library, which serves as a safer cultural outlet, and the number of movies watched through digital media increased. Remarkably, the results from quantile count regression suggest that frequent goers were more affected. However, there is preliminary evidence indicating an exception for ‘very frequent goers’ (highly engaged individuals at the 90th percentile level from the bottom) who may not have much compromised their consumption of culture and arts despite the challenging circumstances brought on by the pandemic.
Keywords: COVID-19; Cultural economics; Culture and arts; Quantile count regression; South Korea